Analisis Struktur Frasa, Klausa, dan Kalimat pada Komentar Netizen TikTok: Kajian Sintaksis Bahasa Indonesia di Media Sosial - Adika Indah Dewi; Ema Nirwana (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyse the structure of phrases, clauses, and sentences in comments made by TikTok users as examples of Indonesian syntax usage on social media. This study focuses on three TikTok videos, each of which discusses the topics of humour, Teacher's Day celebrations, and criticism of the education system. The method used is a descriptive qualitative approach with content analysis techniques to find syntactic patterns in the data. The results show that comments containing humorous themes tend to use ellipsis, incomplete sentences, and fragmentary sentence structures, which serve to emphasise the humorous effect of the comments. In videos with a Teacher's Day theme, comments tended to be formed from complex clauses and conveyed personal feelings and experiences, as well as using evaluative sentences to express complaints or experiences. Meanwhile, in videos containing criticism of education, critical questions, overly long sentences, and complex arguments were found. In general, this study shows that the syntactic form in TikTok comments changes according to the emotional and social context of the content, and demonstrates the flexibility of the Indonesian language in communicating in the digital world. These findings are expected to enrich linguistic studies on social media and provide a deeper understanding of syntactic phenomena today.